2008
DOI: 10.1002/chir.20677
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation performance of micrometer‐sized monodispersed silica spheres with high protein loading

Abstract: Micrometer-sized monodispersed silica spheres (approximately 360 microm) with high loading of bovine serum albumin (BSA) (approximately 450 mg/g) were prepared as an adsorbent for large-scale chiral separation. The new adsorbent was characterized with scanning electron microscopy (SEM), nitrogen adsorption-desorption isotherms, the mercury intrusion method, infrared spectroscopic analysis, and elementary analysis. The extent of chiral separation was tested with rac-tryptophan (rac-Trp) and rac-phenylalanine (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Advantages of using protein-based CSPs include their tendency to be able to work with a broad range of chiral compounds, their ability to be used with aqueous mobile phases, and their ability to directly analyze most chiral compounds without the need for derivation [17,19,22,27]. However, protein-based CSPs can also have a low loading capacity, be expensive to prepare, and have limited stability, which makes these of greater interest for analytical work than for preparative separations [17,19,28,29]. …”
Section: Introductionmentioning
confidence: 99%
“…Advantages of using protein-based CSPs include their tendency to be able to work with a broad range of chiral compounds, their ability to be used with aqueous mobile phases, and their ability to directly analyze most chiral compounds without the need for derivation [17,19,22,27]. However, protein-based CSPs can also have a low loading capacity, be expensive to prepare, and have limited stability, which makes these of greater interest for analytical work than for preparative separations [17,19,28,29]. …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, SAs have emerged as a class of ideal chiral selectors because they are one of the most abundant and extensively studied proteins in the circulatory system . SAs have been widely applied to various chiral discrimination processes, such as high‐performance liquid chromatography (HPLC), affinity ultrafiltration, affinity capillary electrophoresis, and thin‐layer chromatography . The degree and preference of stereoselective drug‐binding processes are not necessarily constant among species.…”
Section: Introductionmentioning
confidence: 99%
“…2 SAs have been widely applied to various chiral discrimination processes, such as high-performance liquid chromatography (HPLC), affinity ultrafiltration, affinity capillary electrophoresis, and thin-layer chromatography. [3][4][5][6] The degree and preference of stereoselective drug-binding processes are not necessarily constant among species. I. Fitos et al 7 investigated stereoselective binding of benzodiazepine and coumarin drugs to SAs from human and six mammalian species by chiral chromatographic technique, and they found that the binding stereoselectivity of tofisopam in humans was opposite to that in all other species (dog, bovine, horse, pig, rabbit, and rat).…”
Section: Introductionmentioning
confidence: 99%
“…(Zhai et al 2009) It is probably because that in this work, the Schiff's base reaction mainly occurred at the droplet surface. Therefore, most of the free aldehydic groups exist on the sphere surface and so does the grafted BSA.…”
Section: Chemically Grafting Bsa On Hybrid Spheresmentioning
confidence: 96%
“…The amino groups on protein surface are the most common used groups Thus we can use the Schiff's base reaction between aldehydic group and amino group to chemically graft protein on hybrid spheres. In our previous work, we have utilized the Schiff's base reaction to immobilize BSA on silica spheres via a three-step method for chiral separation (Zhai et al 2009). Besides its application in chiral separation, BSA can also serve as a model protein to investigate the microspheres' performance on protein immobilization.…”
Section: Chemically Grafting Bsa On Hybrid Spheresmentioning
confidence: 99%